[tex]y^2-y+2y-2=(y^2-y)+(2y-2)=y(y-1)+2(y-1)=(y-1)(y+2)\\\\4a^2-c^2=(2a)^2-c^2=(2a-c)(2a+c)\\\\ab^2+2ab+a^3=a(b^2+2b+a^2)[/tex]
[tex]\displaystyle 1)y^2-y+2y-2=y(y-1)+2(y-1)=(y-1)(y+2)\\\\2)4a^2-c^2=2^2a^2-c^2=(2a)^2-c^2=(2a-c)(2a+c)\\\\3)ab^2+2ab+a^3=a(b^2+2b+a^2)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]y^2-y+2y-2=(y^2-y)+(2y-2)=y(y-1)+2(y-1)=(y-1)(y+2)\\\\4a^2-c^2=(2a)^2-c^2=(2a-c)(2a+c)\\\\ab^2+2ab+a^3=a(b^2+2b+a^2)[/tex]
[tex]\displaystyle 1)y^2-y+2y-2=y(y-1)+2(y-1)=(y-1)(y+2)\\\\2)4a^2-c^2=2^2a^2-c^2=(2a)^2-c^2=(2a-c)(2a+c)\\\\3)ab^2+2ab+a^3=a(b^2+2b+a^2)[/tex]